Synthesis and study of properties of filter media based on modified steelmaking slags for wastewater treatment from anthropogenic pollutants - A. S. Panasyugin; A. R. Tsyganov; N. P. Masherova; N. D. Pavlovsky (Литьë и металлургия, 2025)
Currently, the processes of applying protective coatings to the surface of steel products are widely used – bronzing, latuning, etc. These operations are performed by thermocatalytically applying lead compounds to the surface of steel products, followed by reliable fixation of a layer of bronze, brass, etc. on this substrate. Taking into account subsequent technological operations, a significant amount of circulating, washing and wastewater containing a sufficiently large number of dissolved compounds is formed.